A Defence of Average Utilitarianism. Issue 4 (20th March 2015) - PRESSMAN, MICHAEL
Abstract : Seemingly every theory of population ethics is confronted with unpalatable implications. While various approaches to the subject have been taken, including non-consequentialist approaches, this area has been dominated by utilitarian thought. The two main approaches to population ethics have been total utilitarianism ('TU') and average utilitarianism ('AU'). According to TU, we should seek to bring about the state of affairs that maximizes the total amount of happiness. According to AU, we should seek to bring about the state of affairs that maximizes average per capita happiness. Both theories have been afflicted by seemingly strong objections, and as a result, numerous variations and hybrids have been introduced. Despite the widespread disagreement in the field, though, a near consensus has developed in rejecting AU as an absurd view. In this article, however, I will go against the grain and argue that AU is the theory of population ethics that we should endorse.